Personal Selling Strategy in an Effort to Increase the Number of Mudharabah Savings Customers at BMT Amanah Ummah Surabaya - Majid Abdul Majid; Muhammad Nuruddin (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2023)
Personal selling strategy strategy in increasing the number of mudharabah savings customers and to find out what factors were an obstacle when doing personal seling on mudharabah savings customers at BMT Amanah Ummah Surabaya. This typeof research is a qualitative research with a descriptive approach, using primary data, namely conducting observations, interviews with the head manager of BMT Amanah Ummah, and documentation. and through secondary data sources by obtainingdocuments from BMT Amanah Ummah, checking the validity of this research data using a focus on testing the credibility of the data which is done by triangulation.